English Translation Errors in Abstracts of Educational Administration Students of Post Graduate School of State University of Medan - Yudi Setiawan (JOURNAL OF EDUCATION, 2014)
This study aimed at: (1) investigating the types of translation errors in abstracts, (2) ascertaining the dominant type, and (3) contextualizing the use of the dominant type. This study was classified as descriptive qualitative research. The data were obtained from the thesis abstracts of Educational Administration students of the Post Graduate School of State of the University of Medan. The data were analyzed by classifying them into two types of errors, namely grammatical errors and content errors. The proportion of each type was converted into percentages. The results of this study were as follows: (1) in the grammatical error type, the use of verb group took 58%, and (2) in the content error type, presentation of different senses took 38%. The dominant type of grammatical errors was  caused by the confusion of verb groups in dealing with the English grammar systems. The dominant type of content errors was caused by the failure in choosing appropriate words. This is because of the lack of vocabulary mastery